1989
DOI: 10.1063/1.859093
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap current and parallel viscosity in the low collisionality regime in toroidal plasmas

Abstract: Bootstrap currents in the low collisionality regime in nonaxisymmetric toroidal plasmas are calculated analytically using a model drift kinetic equation. The results obtained using the analytic expression are compared with those calculated from the numerical solutions of the drift kinetic equation. Qualitatively and quantitively, the results are in reasonable agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 7 publications
2
43
0
Order By: Relevance
“…Therefore, the toroidal period numbers assumed there were mainly N = 10, and the assumed B (Boozer) mn [B = ΣB mn cos(mθ − nNζ)] spectra did not include n 0, 1. Although the theory treating the non-bounce-averaged guiding center motion [3,4] is applicable basically for arbitrary B mn spectra, arbitrary aspect ratios, and arbitrary rotational transform per toroidal period ι/N [17], the benchmarking examples for cases with n 0, 1, lower aspect ratios, and larger ι/N had not been reported. A more important open issue is the ripple-trapped/untrapped boundary layer.…”
Section: Inroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the toroidal period numbers assumed there were mainly N = 10, and the assumed B (Boozer) mn [B = ΣB mn cos(mθ − nNζ)] spectra did not include n 0, 1. Although the theory treating the non-bounce-averaged guiding center motion [3,4] is applicable basically for arbitrary B mn spectra, arbitrary aspect ratios, and arbitrary rotational transform per toroidal period ι/N [17], the benchmarking examples for cases with n 0, 1, lower aspect ratios, and larger ι/N had not been reported. A more important open issue is the ripple-trapped/untrapped boundary layer.…”
Section: Inroductionmentioning
confidence: 99%
“…However, the covering area of the neoclassical theory includes various collisionality regimes and also plasma flows. In calculation of the flows, the field particle portion is indispensable in general collisionality regimes, and thus the moment equation approach for non-symmetric toroidal plasmas was developed mainly for neoclassical parallel flows and the associated parallel viscosity [3][4][5][6]. Although Sugama and Horton [7] showed that a consistent frame work including both flows and radial diffusions (in other words, not only the parallel viscosity but also poloidal and toroidal viscosities) can be constructed in this line of moment approach, methods for calculating all the required viscosity coefficients in general collisionality regimes in general toroidal configurations had not been shown.…”
Section: Inroductionmentioning
confidence: 99%
“…19 For parameters typical of QH mode pedestals with normalized collision frequency ν * = 0.05 and inverse aspect ratio r/R = 0.3, the bootstrap current is approximately 80%-90% of the collisionless limit. 20 In addition, numerical calculations find that there are modest modifications due to finite poloidal gyroradius 20 (which 3 have yet to be evaluated for QH modes).…”
Section: Numerical Schemementioning
confidence: 99%
“…5 is that the polodial magnetic field is offset vertically indicating that there is a current flowing in the plasma in addition to the PfirschSchlüter current. We have made estimates of the bootstrap current in HSX using the BOOTSJ code [13] using the data from the Thomson scattering array as input. However, since the magnetic diffusion time is generally greater than the ECH pulse length, the total current measured by the Rogowski coil has not reached a steady-state by the end of the discharge.…”
Section: Pfirsch-schlüter and Bootstrap Currentsmentioning
confidence: 99%